Relationships between health personality and death anxiety: mediating role of death coping self-efficacy among Chinese clinical medical freshmen - Junping Zhong; Xiao Li; Yiming Zhou; Huohuo Dai; Deling Zhang; Huili Chen; Tianya Wang; Enming Zhang; Zhijie Zou; Qiuxiang Chen; Qing Zhang (BMC Palliative Care)
Abstract Background Death anxiety in physicians is considered to be a possible factor affecting the quality of palliative care. As the reserve force of future medical careers, the level of death anxiety among clinical medical freshmen and its impact mechanism deserves attention. Previous studies have indicated that personality traits and self-efficacy may be factors influencing death anxiety. However, there is limited research on the current state of death anxiety among clinical medical freshmen, and the impact of health personality, death coping self-efficacy on death anxiety. The objectives of this study were to investigate the death anxiety levels of clinical medical freshmen, explore whether death anxiety is affected by health personality and death coping self-efficacy, and examine whether death coping self-efficacy mediates the association between health personality and death anxiety among clinical freshmen. Methods A cross-sectional survey among 378 clinical medical freshmen was conducted at a university in Wuhan, Hubei Province, China between June and July 2023. Demographic questionnaire, the Chinese versions of the Health Personality Assessment (HPA), Death Coping Self-efficacy Scale (DCSS) and Death Anxiety Scale (DCS) were used. SPSS 25.0 statistical software was used for descriptive analysis, independent sample t-tests, one-way ANOVA, and Pearson correlation analysis. The mediating effect analysis was performed with PROCESS version 4.1 Model. Results A total of 360 valid questionnaires were collected. Clinical medical freshmen exhibited high levels of death anxiety was (45.55 ± 7.57). Health neuroticism has a significant positive impact on death anxiety (β = 0.407, t = 2.323, P < 0.05). In contrast, death anxiety was significantly impacted negatively by death coping self-efficacy (β=-0.105, t=-3.441, P < 0.05). The association between health neuroticism and death anxiety was partially mediated by death coping self-efficacy; the mediating impact accounted for 18.44% of the total effect, with a 0.092 coefficient. Conclusions This study revealed that clinical medical freshmen had high levels of death anxiety. Health neuroticism and death coping self-efficacy directly affected clinical medical freshmen’ death anxiety. Death coping self-efficacy mediated the relationship between health neuroticism and death anxiety among clinical medical freshmen. Interventions by medical educators that focus on both individuals’ health personality and death coping self-efficacy may be most effective in reducing death anxiety among clinical medical freshmen.